Evaluation of The Implementation of Physical Education Learning Using The CIPP Model at SMAN Kesamben - Hudanuddin Mufid; Rahayu Prasetiyo; Ilmul Maarif; Arsika Yunarta (PHEDHERAL, 2024)
This type of evaluative research uses the CIPP (Context, Input, Process, Product) evaluation model to determine the implementation of Physical Education learning at Kesamben State High School. The subjects in this study are all teachers of Physical Education subjects at Kesamben State High School, which totals three teachers. Data collection was carried out using observation, interview, and documentation techniques. Descriptive methods analyze quantitative and qualitative data. The purpose of this study is to find out (1) the completeness of the learning tools and the suitability of the context of the content of the lesson plan and teaching modules; (2) the Background qualifications of Physical Education subject teachers and the suitability of Physical Education facilities and infrastructure; (3) The process of Physical Education learning activities; (4) Students' learning achievement as seen from the daily grades of Physical Education subjects. The results of the study showed that: (1) Context Evaluation, the completeness of learning tools is almost all available, but some documents are not yet available, namely the curriculum guidebook (Class X, XII, XII) and the attitude assessment rubric (For Class XI), while for the suitability of the context of the content of the Teaching Module received a score of 14 out of a maximum score of 17. Suppose the percentage is 88.8% appropriate. Meanwhile, for the suitability of the context of the content of the RPP for grades XI and XII, they scored 28 and 30, respectively and were included in the good category. (2) Input Evaluation: it is known that the background of Physical Education teachers at Kesamben State High School is in accordance with the qualification standards of teaching teachers. The suitability of the context of Physical Education facilities and infrastructure shows a level of conformity of 42.5%, which is included in the category of quite good. (3) Process Evaluation, which includes Physical Education learning activities, received an average score of 86.5% and was included in the Good category. (4) Product Evaluation, namely the learning outcomes of students who received an average score for class X: 80.2, Class XII: 87.81, and class XII: 89.82 and were included in the good category. This study concludes that, in general, the implementation of PHYSICAL EDUCATION learning at Kesamben State High School has met the standards. However, not all of them are in accordance with the suitability of learning tools and the context of the content of the Teaching Module and RPP, as well as Physical Education facilities and infrastructure.